Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the value of the polynomial [tex]\(2x^3 - 3x^2 + 7\)[/tex] at [tex]\(x = 2\)[/tex] and [tex]\(x = -1\)[/tex], we need to substitute these values of [tex]\(x\)[/tex] into the polynomial and simplify. Let's go through each step-by-step.
### Evaluating the polynomial at [tex]\(x = 2\)[/tex]
1. Step 1: Substitute [tex]\(x = 2\)[/tex] into the polynomial
[tex]\[ 2(2)^3 - 3(2)^2 + 7 \][/tex]
2. Step 2: Calculate the cubed term [tex]\(2^3\)[/tex]
[tex]\[ 2^3 = 8 \implies 2 \cdot 8 = 16 \][/tex]
3. Step 3: Calculate the squared term [tex]\(2^2\)[/tex]
[tex]\[ 2^2 = 4 \implies 3 \cdot 4 = 12 \][/tex]
4. Step 4: Combine the results
[tex]\[ 16 - 12 + 7 = 11 \][/tex]
So, the value of the polynomial at [tex]\(x = 2\)[/tex] is [tex]\(11\)[/tex].
### Evaluating the polynomial at [tex]\(x = -1\)[/tex]
1. Step 1: Substitute [tex]\(x = -1\)[/tex] into the polynomial
[tex]\[ 2(-1)^3 - 3(-1)^2 + 7 \][/tex]
2. Step 2: Calculate the cubed term [tex]\((-1)^3\)[/tex]
[tex]\[ (-1)^3 = -1 \implies 2 \cdot (-1) = -2 \][/tex]
3. Step 3: Calculate the squared term [tex]\((-1)^2\)[/tex]
[tex]\[ (-1)^2 = 1 \implies 3 \cdot 1 = 3 \][/tex]
4. Step 4: Combine the results
[tex]\[ -2 - 3 + 7 = 2 \][/tex]
So, the value of the polynomial at [tex]\(x = -1\)[/tex] is [tex]\(2\)[/tex].
### Summary of Results
- The value of the polynomial [tex]\(2x^3 - 3x^2 + 7\)[/tex] at [tex]\(x = 2\)[/tex] is [tex]\(11\)[/tex].
- The value of the polynomial [tex]\(2x^3 - 3x^2 + 7\)[/tex] at [tex]\(x = -1\)[/tex] is [tex]\(2\)[/tex].
Thus, the values are:
[tex]\[ \boxed{(11, 2)} \][/tex]
### Evaluating the polynomial at [tex]\(x = 2\)[/tex]
1. Step 1: Substitute [tex]\(x = 2\)[/tex] into the polynomial
[tex]\[ 2(2)^3 - 3(2)^2 + 7 \][/tex]
2. Step 2: Calculate the cubed term [tex]\(2^3\)[/tex]
[tex]\[ 2^3 = 8 \implies 2 \cdot 8 = 16 \][/tex]
3. Step 3: Calculate the squared term [tex]\(2^2\)[/tex]
[tex]\[ 2^2 = 4 \implies 3 \cdot 4 = 12 \][/tex]
4. Step 4: Combine the results
[tex]\[ 16 - 12 + 7 = 11 \][/tex]
So, the value of the polynomial at [tex]\(x = 2\)[/tex] is [tex]\(11\)[/tex].
### Evaluating the polynomial at [tex]\(x = -1\)[/tex]
1. Step 1: Substitute [tex]\(x = -1\)[/tex] into the polynomial
[tex]\[ 2(-1)^3 - 3(-1)^2 + 7 \][/tex]
2. Step 2: Calculate the cubed term [tex]\((-1)^3\)[/tex]
[tex]\[ (-1)^3 = -1 \implies 2 \cdot (-1) = -2 \][/tex]
3. Step 3: Calculate the squared term [tex]\((-1)^2\)[/tex]
[tex]\[ (-1)^2 = 1 \implies 3 \cdot 1 = 3 \][/tex]
4. Step 4: Combine the results
[tex]\[ -2 - 3 + 7 = 2 \][/tex]
So, the value of the polynomial at [tex]\(x = -1\)[/tex] is [tex]\(2\)[/tex].
### Summary of Results
- The value of the polynomial [tex]\(2x^3 - 3x^2 + 7\)[/tex] at [tex]\(x = 2\)[/tex] is [tex]\(11\)[/tex].
- The value of the polynomial [tex]\(2x^3 - 3x^2 + 7\)[/tex] at [tex]\(x = -1\)[/tex] is [tex]\(2\)[/tex].
Thus, the values are:
[tex]\[ \boxed{(11, 2)} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.